Kimura Disease: A Detailed Analysis of Clinical and Radiological Manifestations in a Retrospective Case Series - Zhao F; Zhou M; Mao A; Zhang Y; Chen Y (Dove Medical Press, 2024)
Fanfan Zhao,1 Min Zhou,2 An Mao,3 Yingjiao Zhang,4 Yao Chen2 1Center for Rehabilitation Medicine, Department of Radiology, Zhejiang Provincial People's Hospital (Affiliated People's Hospital), Hangzhou Medical College, Hangzhou, Zhejiang Province, People's Republic of China; 2Department of Radiology, 903 Hospital of the Joint Service Support Force of the Chinese People's Liberation Army, Hangzhou, Zhejiang Province, People's Republic of China; 3Department of Outpatient, 903 Hospital of the Joint Service Support Force of the Chinese People's Liberation Army, Hangzhou, Zhejiang Province, People's Republic of China; 4Department of Gastroenterology, 903 Hospital of the Joint Service Support Force of the Chinese People's Liberation Army, Hangzhou, Zhejiang Province, People's Republic of ChinaCorrespondence: Yao Chen, Department of Radiology, 903 Hospital of the Joint Service Support Force of the Chinese People's Liberation Army, Hangzhou, Zhejiang Province, People's Republic of China, Email chenyao19970712@163.comBackground: Kimura disease (KD) is a rare chronic inflammatory disease that affects mainly young Asian men and is characterized by painless subcutaneous masses, lymphadenopathy, and elevated serum IgE levels. Despite its benign nature, KD poses a diagnostic and therapeutic challenge due to its rarity and clinical variability.Objective: This study aimed to provide a comprehensive analysis of the clinical and radiological features of KD in a retrospective case series, to assess treatment outcomes, and to discuss the implications for diagnosis and management.Methods: We retrospectively analyzed four histologically confirmed cases of KD admitted to Zhejiang Provincial People's Hospital from January 2018 to October 2023. Clinical and radiological data were retrospectively analyzed, and imaging findings were analyzed by two neuroradiologists to determine lesion characteristics and contrast enhancement patterns.Results: Our findings showed that the patients were predominantly male, with a mean age of 43 years and an age range of 13- 71 years. All patients presented with painless subcutaneous masses and three of them had peripheral blood eosinophilia and elevated serum IgE levels. Radiographically, the lesions were predominantly ill-defined with heterogeneous enhancement, accompanied by subcutaneous fat atrophy. Complete surgical excision and oral corticosteroids were effective treatments, and no recurrence was noted during follow-up.Conclusion: KD should be considered in the differential diagnosis of painless subcutaneous masses in the head and neck region, especially in the presence of eosinophilia and elevated IgE levels. Our findings contribute to the understanding of KD's clinical and radiological spectrum and highlight the need for long-term follow-up due to the risk of recurrence.Keywords: Kimura disease, computed tomography, CT, magnetic resonance imaging, MRI, eosinophilia